Language-Based Modulation of the Stream/Bounce Judgment. (June 2020) - Cui, Shengbin; Ariga, Atsunori
When two identical objects on a screen move toward each other, coincide at the center of the screen, and then continue to move along their original trajectories to the opposite starting points, observers perceive these visual stimuli as showing one of the two possible scenarios: streaming through or bouncing off each other (stream/bounce perception). Previous research has shown that when a high-arousal face is presented along with the two moving objects, the bouncing percept was predominant, as compared with when a middle- or low-arousal face is presented. In this study, however, such a modulatory effect of the emotional face was eliminated when participants did not judge stream or bounce and the terms "bouncing/streaming" were not used in the experiments. These results suggest that the modulatory effect of emotional stimuli on the stream/bounce judgment cannot be explained solely by the emotional processing per se but, rather, can be modulated by language-based processing.